Piperine-loaded chitosan nanoparticles: preparation and characterization - Nhi, Tran Thi Y; Trinh, Cong Duc; Pham, Hanh Bich; Quang, Tuan Le; Lai, Thuy Thi; Le, Ha Thi Thanh; Truong, Thien Do (Vietnam Journal of Science and Technology, 2021)
Abstract – HCTN7. Plasma cholesterol level plays an important role in atherosclerosis and cardiovascular diseases. Piperine, an alkaloid form of black pepper is known to reduce cholesterol uptake. In this paper, piperine-loaded chitosan nanoparticles (CTS-PIP NPs) were prepared by ionic gelation method. Molecular interactions among the components were confirmed by FT-IR spectroscopy. Transmission electron microscopy (TEM) images revealed spherical-shaped nanoparticles with diameter of <100 nm. CTS-PIP NPs displayed positive ζ-potential(ZP) of about 31.6 mV. Dynamic light scattering (DLS) particle size (PS) distribution analysis indicated the mean particle size of CTS-PIP NPs was 245.9 nm, polydispersity index of 31%